Staged ridge-split evaluated using cone beam computed tomography and peri-implant plastic surgery in the mandibular arch - Jain, Nikhil Vasant; Shinde, Purva H.; Poplai, Gaurav R.; Gharatkar, Affaf A. (European Journal of General Dentistry, 2015)
Lack of sufficient bone to place an implant at a functionally and an esthetically appropriate position is a common problem, especially in the mandibular posterior region. Narrow edentulous alveolar ridges <5 mm wide require bone augmentation before implant placement to establish a bony wall of at least 1 mm around the endosseous implant. Various surgical widening techniques are available, including lateral augmentation with or without guided bone regeneration, ridge-split technique and horizontal distraction osteogenesis. The ridge-split technique aims at creating a new implant bed by longitudinal osteotomy of the alveolar bone. The buccal cortex is repositioned laterally by greenstick fracture, and the space between the buccal and lingual cortices is filled with a graft material. Peri-implant plastic surgery focuses on harmonizing peri-implant structures by means of hard- and soft-tissue engineering and includes bone structure enhancement, soft-tissue enhancement, precision in implant placement and improves quality of the prosthetic restoration. The rationale for the peri-implant plastic surgery approach goes well beyond pure esthetics as it creates peri-implant keratinized mucosa and interimplant soft-tissue height in order to avoid food impaction, interimplant airflow, and speech problems. This case report demonstrates a staged ridge-split technique evaluated with cone beam computed tomography using a piezosurgical unit and a surgical technique to restore a papilla-like tissue at the time of the second-stage implant surgery.
Keywords: Alveolar ridge; cone beam computed tomography; grafting; peri-implant plastic surgery; piezosurgery; ridge-split